Comparison of the white image and cultural implication on The Injustice of Dou E and The Princess of Mahsuri / Lee Hau - Lee, Hau (2021)
The Injustice to Dou E is a China Yuan poetic drama masterpiece whereas The Princess of Mahsuri is Malaysia's folk legend. Although both stories represent different theme, they have the same motif of "injustice death". Both heroines took three supernatural oaths to show their innocence after being wronged. Although the two stories are similar in content, it is worth to note that three oaths of the two have invariably used white. This article attempts to explore the different white images and cultural implication of two places from the cultural differences caused by historical, ethnic, and geographical factors by emphasizing on the interpretation of colours in different culture. The purpose of this is to find the unique values of respective culture and to achieve cross-cultural exchange and communication. In addition, the social significance behind the two stories is also worth of further studies